Mathematical comparison of defuzzification of fuzzy logic controller for smart washing machine (Journal of Bangladesh Academy of Sciences, 2022)
This is the age of modern science where different kinds of gadgets are used for the betterment of humanity. Various electronic, intelligence systems are invented via modern technology where FLC (Fuzzy Logic Controller) is used to develop their intelligence systems. Nowadays, FLC is widely used in uncertainty and robust development systems. Two inputs and one output have been used in this paper. Also, various defuzzification methods are used to determine the washing time of a smart washing machine. Finally, the performance of the various defuzzification methods has been compared mathematically. This work has been simulated by using the MATLAB toolbox.J. Bangladesh Acad. Sci. 46(1); 1-8: June 2022